IMPLEMENTASI PEACE EDUCATION DALAM KURIKULUM - Chaterina Puteri Doni; Sriwahyuningsih R Saleh (IKIP PGRI Jember, 2017)
This research was used qualitative approach with the study case design. Collective the data was collected through interviews, observation and documentation. Techniques of analyzing the data are eduction of data, data presentation and conclusion. The informants in this research are the rector of UMG, lecturers, and students.The result were expected at describing implementation of principal and concepts of peace education in curriculum of UMG, also the result of this research will be used to create UMG as center of peace education at Gorontalo province. Finally, peace can be maintained in Gorontalo province. And will always enlighten the people through peace education.